Psychological factors and health-related quality of life in fibromyalgia patients - Campos, Ricardo (2024)
Fibromyalgia (FM) has been associated with decreased health-related quality of life (HRQoL), which has been linked to psychological variables such as anxiety, depression, coping, and social support. This study aimed to simultaneously analyse the association of these variables with HRQoL in FM patients and explore their mediating role in the relationship between somatic symptoms and HRQoL. participants and procedure A cross-sectional sample of 134 FM patients (97% women) with no other rheumatologic diseases followed in specialized healthcare services completed self-report questionnaires to evaluate pain, fatigue, sleep, anxiety, depression, coping, social support, and HRQoL. results The results indicated that FM patients experienced a negative impact on all dimensions of HRQoL, with anxiety primarily affecting the mental dimensions, and depression and social support affecting both physical and mental dimensions. Anxiety, depression, dysfunctional coping, and low social support were independent predictors of HRQoL and mediated the effect of somatic symptoms in the mental component of HRQoL. conclusions FM patients experience a negative impact on HRQoL, and anxiety, depression, coping and social support play an important role as independent predictors of this decrease, and as mediators of the effect of somatic symptoms in the mental dimensions of HRQoL. This underscores the importance of considering these psychological variables in the therapeutic approach to FM and suggests the need for interventions targeting anxiety, depression, dysfunctional coping, and low social support to improve HRQoL in FM patients